REVIEW: PELUANG MAHKOTA DEWA SEBAGAI ANTIKANKER - Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2012)
Abstract: In order to be used in formal health care systems, medicinal plants have to be safe anddisplay promising pharmacological effects. Mahkota dewa is well known as a traditionalmedicine in Indonesia. In folk medicine, its fruits and leaves are used to relief cancer, impotency,hypoglycemic, hypotensive, antirheumatic, liver and kidney disorders and skin disorders.According to pharmacology and toxicology studies especially on cytotoxic effects, mahkota dewahas anticancer activity. However, further studies will be required to establish the cell target foranticancer treatment.Key words: mahkota dewa, anticancer, cytotoxic